2001
DOI: 10.1081/css-100104109
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide for Surface Irrigation to Increase Nutrient-Use Efficiency and Protectwater Quality

Abstract: Furrow irrigation systems have a greater application capacity, are less costly, and use less energy than sprinkler systems but furrow irrigation produces greater runoff, erosion, and deep percolation losses. Phosphorus (P) and nitrogen (N) losses are associated with runoff sediment, and can be minimized by eliminating irrigationinduced erosion. Excessive leaching of inorganic and organic solutes commonly occurs at the inflow region of furrow irrigated fields where infiltration opportunity times are longer. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 26 publications
(36 reference statements)
3
30
1
Order By: Relevance
“…The most significant environmental effect of PAM use is its erosion reduction, protecting surface waters from sediment and other contaminants washed from eroding fields. PAM greatly reduces nutrients, pesticides, and biological oxygen demand (BOD) of irrigation return flows (Agassi et al, 1995;Lentz et al, 1998Lentz et al, , 2001. In Australian tests of PAM, sediment, nutrient, and pesticide reductions exceeded levels achieved by traditional conservation farming methods (Waters et al, 1999a, b).…”
Section: Environmental and Safety Concernsmentioning
confidence: 99%
“…The most significant environmental effect of PAM use is its erosion reduction, protecting surface waters from sediment and other contaminants washed from eroding fields. PAM greatly reduces nutrients, pesticides, and biological oxygen demand (BOD) of irrigation return flows (Agassi et al, 1995;Lentz et al, 1998Lentz et al, , 2001. In Australian tests of PAM, sediment, nutrient, and pesticide reductions exceeded levels achieved by traditional conservation farming methods (Waters et al, 1999a, b).…”
Section: Environmental and Safety Concernsmentioning
confidence: 99%
“…Wetting fronts are broader and infiltration is higher in the rows treated with polyacrylamide as compared with those that are untreated (Yu et al, 2003). The use of PAM as alternative practice of soil conservation has been repeatedly proven to be an effective and viable (Bjorneberg et al, 2000;Santos et al, 2000;Lentz et al, 2001;Yu et al, 2003;Kornecki et al 2005;Shrestha et al, 2006;Chávez, 2007;Chavez et al, 2009). However, this effectiveness depends on the type and charge density and molecular weight (Green et al, 2001).…”
mentioning
confidence: 99%
“…Several studies have shown that PAM dissolved in irrigation water at a rate of 10 kg ha -1 improves water infiltration (Leib et al, 2005;Chávez et al, 2010) and may be increased from 7 to 8 times the final infiltration as compared with the control (Ajwa & Trout, 2006). However, at rate of 20 kg ha -1 applied in granular was this has proven to be effective in controlling erosion (Lentz & Sojka, 2000;Chávez et al, 2009), if applied in the first 5 mm of soil, it will reduce runoff by up to 30% as compared with the control plot (Yu et al, 2003), and may be increased by up to 54% of the aggregates stability (Lentz et al, 2001;Shrestha et al, 2006). According to Leib et al (2005) polyacrylamide application prior to irrigation control the erosion caused by concentrated flow in furrow irrigation systems, reducing soil detachment caused by hydraulic shear stresses.…”
mentioning
confidence: 99%
See 2 more Smart Citations